2009
DOI: 10.1111/j.1365-2958.2009.06872.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of choline‐utilization proteins in Streptococcus pneumoniae using novel fluorescent reporter systems

Abstract: SummaryThe molecular mechanisms underlying cell growth, cell division and pathogenesis in Streptococcus pneumoniae are still not fully understood. Single-cell methodologies are potentially of great value to investigate S. pneumoniae cell biology. Here, we report the construction of novel plasmids for single and double cross-over integration of functional fusions to the gene encoding a fast folding variant of the green fluorescent protein (GFP) into the S. pneumoniae chromosome. We have also established a zinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 63 publications
2
95
0
Order By: Relevance
“…With this tool we showed that S. pneumoniae DivIVA localizes to both the cell division sites and the cell poles (35). We now show that StkP also localizes to the midcell and that this localization pattern depends on its extracellular PASTA domains.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…With this tool we showed that S. pneumoniae DivIVA localizes to both the cell division sites and the cell poles (35). We now show that StkP also localizes to the midcell and that this localization pattern depends on its extracellular PASTA domains.…”
mentioning
confidence: 79%
“…To determine the localization and dynamics of StkP in living cells, we constructed an N-terminal gfpstkP fusion (Fig. 1A) by using vector pJWV25, which integrates by double-crossover in the chromosome at the nonessential bgaA locus and harbors the zinc-inducible P Zn promoter (35). The resulting construct then was introduced into three closely related well-characterized and widely used S. pneumoniae strains: the encapsulated D39 and nonencapsulated R6 and Rx1 genetic backgrounds (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all S. pneumoniae strains tested so far have been unable to grow on fucose as a sole carbon and energy source, the role of this sugar in pneumococcal metabolism remains unclear (3). An alternative method based on the Zn 2ϩ -inducible promoter P czcD was described recently (7,17). To perform a gene depletion experiment with the Zn 2ϩ system, a DNA cassette containing a selectable antibiotic resistance marker and the gene of interest under the control of the P czcD promoter was inserted into the FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The pJVW25 plasmid was used to express RrgC, Srt-C1, and Srt-C3 in pneumococcal strains (30). Protein expression was under the control of the zinc-inducible PczcD promoter and required addition of 0.15 mM ZnCl 2 in the liquid medium.…”
Section: Methodsmentioning
confidence: 99%